ANALISIS KEMAMPUAN DALAM MENYELESAIKAN SOAL CERITA MENGGUNAKAN PENDEKATAN PROBLEM SOLVING PADA MATERI PERKALIAN DI KELAS III SDN 1 SAYAN - Rahmayanti Putri; Yumi Sarassanti; Aprima Tirsa (Hipotenusa Journal of Research Mathematics Education (HJRME), 2020)
The purpose of this researc was to describe (1) students ability to complete story test before usedproblem solving approach. (2) students ability to complete story test after used problem solving learning. (3) the significant difference of students ability to complete story test before and after used problem solving approach. This researc was to pre experimental design, and this design is one group pretest-posttest . this research did to the threeth grade students at SDN 1 Saya, there have 24 students with 14 boys and 10 girls. Data analysis on this research are normality test, test of homogenity, paired sample t-test, and n-gain test. The result of this research: (1) Students ability to complete story test before used problem solving approach look on the pretest shown that value average of the students are 42. (2) Students ability to complete story test after used problem solving approach look on the pretest shown that value average of the students are 75.83. (3) It shown that signifanct difference of students ability to complete story test before and after used problem solving approach.Keywords: Ability to complete story test, problem solving.